The Correlation Between Students’ Habit In Listening Song And Students’ English Listening Skill - Nurjanah Nurjanah; Ira Miranti; Nina Dwiastuty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
The purpose of this research is to find out The Correlation between Students’ Habit in Listening Song and Student’s English Listening Skill. The research conducted at the senior high school of Trampil for the twelve grade students. The school is located in East Jakarta. The method used is a survey with correlational analysis. The result of the research are there is positive and significant correlation between students’ habit in listening song and English listening skill. It is shown in the score of Fobserved is 39.286 and Sig is 0.000. The score of Fobserved is more than Ftable (> 3.25), and the score of Sig is less than 0.05 (<0.05). Based on that, we can conclude that the better of students’ habit in listening song, the better students’ listening skill. Keywords: Correlation, Listening Song, English Listening skill.